2014
DOI: 10.1017/s0018246x13000496
|View full text |Cite
|
Sign up to set email alerts
|

Citizenship, War, and the Origins of International Ethics in American Political Philosophy, 1960–1975

Abstract: This article examines a series of debates about civil disobedience, conscription, and the justice of war that took place among American liberal philosophers, lawyers, and activists during the civil rights movement and the Vietnam War. It argues that these debates fundamentally reshaped American political philosophy, by shifting the focus from the welfare state to the realm of international politics. In order to chart this transition from the domestic to the international, this article focuses on the writings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In Rawls's case, while his published political views were submerged in his larger theoretical edifice, it seems clear that his assessment of the contentious debates and social change of this period was far more sympathetic than Buchanan's. 69 These differences first became evident when Buchanan reviewed A Theory of Justice. Buchanan observed that although, on the basis of Rawls's earlier papers, he had "looked forward to publication of Rawls's long-promised treatise," he in fact found himself "less sympathetic" to Rawls than he thought.…”
Section: Behind the Veilmentioning
confidence: 99%
“…In Rawls's case, while his published political views were submerged in his larger theoretical edifice, it seems clear that his assessment of the contentious debates and social change of this period was far more sympathetic than Buchanan's. 69 These differences first became evident when Buchanan reviewed A Theory of Justice. Buchanan observed that although, on the basis of Rawls's earlier papers, he had "looked forward to publication of Rawls's long-promised treatise," he in fact found himself "less sympathetic" to Rawls than he thought.…”
Section: Behind the Veilmentioning
confidence: 99%
“…It exists in tension with liberal ideas of civic rights against arbitrary violence, non-violent conflict resolution, and individual autonomy. Though the recourse to volunteer militaries has been posited by contemporary liberal thinkers -perhaps paired with a conscript lottery -as alleviating immediate problem of state coercion of individuals, 115 it does not address the underlying normative obligation of service. 116 The confluence of gendered cultural affects, narratives, and ethics regarding (at least potential) military service and citizenship suggests that in a time of war, all "good" masculine citizens ought to serve.…”
Section: Gendered Civilian Anxietymentioning
confidence: 99%
“…"Insofar as civil disobedience theory assumes that political resistance requires moral justification even in the settings that are morally comparable to Jim Crow, it is premised on serious moral error" (Lyons 1998, 39). For discussion of the historical contextthe Civil Rights Movement and the Vietnam War-in which Rawls and Walzer developed their theories of disobedience, see Forrester (2014). 6.…”
Section: Rethinking Civil Disobediencementioning
confidence: 99%